Algae cultivation systems integrated with photovoltaic cell: a systematic review - M. S., N. Atikah; Harun, Razif; Ilyas, R. A.; Norrrahim, Mohd Nor Faiz; Knight, Victor Feizal (Elsevier, 2025)
Microalgae species have recently been focused on biofuel production, such as biodiesel, bioethanol, and biohydrogen. These photosynthetic organisms are widely cultivated in photobioreactors and open ponds. Advances in the cultivation methods, e.g., the development of the open pond-photobioreactor hybrid system, floating, photobioreactor, open pond-photovoltaic, and photobioreactor-photovoltaic are aiming to overcome the limitations of both methods. Among the improvements achieved are lower energy cost due to lower dependency upon electricity from the grid, lesser greenhouse gas emissions, lower raw material cost due to lower evaporative water loss, higher algal biomass productivity, reduced biofouling, easier process control, and the ability of wastewater treatment. However, the systems are also limited by the variation in biomass productivity in different locations and environmental conditions. With further optimization studies, the environmental, economic, and energy aspects of open pond-photovoltaic and photobioreactor-photovoltaic systems can be improved. Overall, the open pond-photovoltaic system offers more diverse benefits than the photobioreactor-photovoltaic system. Nevertheless, both systems are practical for enhanced microalgae cultivation systems due to the fact that the quality, price, and product developments from both methods are different. This paper presents the development of modified open and closed algal cultivation systems, including the integration with photovoltaic cells.